The Phenomenon of Dropout Students in Oil Palm Producing Areas (Study on Children of Oil Palm Farmers in Sambas Regency) - Hasanah, Mahmudah; Rupita, Rupita; Sudirman, Sudirman; Musa, Pabali; Mukhlis, Mukhlis (Cita konsultindo, 2025)
The phenomenon of school dropout among children of oil palm farmers in Karaban Jaya Village, Subah Sub-district, Sambas District shows a complex problem that is not only related to economic aspects, but also influenced by social, psychological and infrastructure factors. This study aims to identify the factors that cause children of oil palm farmers to drop out of school and the impact on their social and psychological development. The research method used is qualitative with a case study approach, through field observations, in-depth interviews, and documentation. The results showed that low interest in learning, limited facilities for secondary education, poor road infrastructure, and the influence of an unfavorable social environment were the main causes. In addition, early symptoms such as inferiority towards outsiders, closed attitudes, low rationality, and laziness in developing themselves were found as strong indications towards the risk of dropping out of school. These findings underscore the importance of holistic interventions involving families, schools, communities and governments in preventing school dropout in palm oil producing villages. This research is expected to serve as a basis for the formulation of social and area-based education policies in order to guarantee children's right to equal and sustainable education.